Fabricating a graphene oxide—bayberry tannin sponge for effective radionuclide removal. (29th April 2016) - Deng, Xiaodong; Liu, Xiaonan; Duan, Tao; Zhu, Wenkun; Yi, Zao; Yao, Weitang
Abstract: Bayberry tannin (BT)–reduced graphene oxide ( r GO) sponges have been prepared by self–assembly, with bayberry tannin serving as both reductant and surface functionalization agent. The synthetic method is based on the self-assembly of graphene oxide (GO) sheets into porous hydrogel structures. By varying the weight ratio of GO to BT, a series of sorbents with different densities of organic molecules have been obtained and applied to remove Sr 2+ from aqueous solutions. Adsorption isotherms (Langmuir and Freundlich) and kinetics (pseudo-first order and pseudo-second order) have been investigated to discuss the sorption performance of r GO/BT sponges. The r GO/BT (w/w 1:1) sponge shows excellent adsorption properties for Sr 2+, with maximum capacities of 67.98 mg g −1 . The adsorption capacity is much higher than those in classic Sr 2+ adsorbents, such as hydrous manganese dioxide, Egyptian soils, Hydroxyapatite nanoparticles, sodium hexa-titanate nanofibers, Graphene oxide, artificially altered phlogopite(Ca–Phl), and PB/Fe3 O4 /GO. Adsorption mechanisms have been examined using the x-ray photoelectron spectra of sorbents before and after Sr 2+ adsorption, and the results indicate that the sorption of Sr 2+ on GO and GO/BT 1.0 is largely depended on oxygen functional groups. The results show that the GO/BT sponge is a promising candidate for adsorbing Sr 2+ ion.